1999
DOI: 10.1152/advances.1999.276.6.s23
|View full text |Cite
|
Sign up to set email alerts
|

"Virtual rat": a tool for understanding hormonal regulation of gastrointestinal function.

Abstract: This manuscript describes a "dry laboratory" using the "virtual rat" to help students understand the hormonal regulation of gastrointestinal function. The laboratory was modeled after a recent exercise that used the virtual rat to teach basic endocrine physiology. The virtual rat concept avoids the many obstacles associated with animal experimentation (for example, lack of adequate animal facilities, expense, equipment, and limited teacher experience). Our goal was to create a fun and educational experience wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…For example, one study reported that the use of computer-aided three-dimensional computer models improved performance in a gross anatomy course in medical school, and the effect was greatest in students that had performed lowest on the practical examinations, suggesting that certain student populations may benefit more from technological tools than others (Miller, 2016). Beginning in the late twentieth century, computer-assisted technologies that simulated physiological processes were found to be an effective learning tool for physiology (Richardson, 1997;Hsu et al, 1999). As three-dimensional rotatable images of human organs became available at the beginning of this century, for example, The Visible Body Project ® (Ackerman, 1998(Ackerman, , 2017NLM, 2019) and The Chinese Visible Body Project (Zhang, et al, 2006), the use of computer-assisted learning became increasingly common as a tool in the anatomy classroom.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study reported that the use of computer-aided three-dimensional computer models improved performance in a gross anatomy course in medical school, and the effect was greatest in students that had performed lowest on the practical examinations, suggesting that certain student populations may benefit more from technological tools than others (Miller, 2016). Beginning in the late twentieth century, computer-assisted technologies that simulated physiological processes were found to be an effective learning tool for physiology (Richardson, 1997;Hsu et al, 1999). As three-dimensional rotatable images of human organs became available at the beginning of this century, for example, The Visible Body Project ® (Ackerman, 1998(Ackerman, , 2017NLM, 2019) and The Chinese Visible Body Project (Zhang, et al, 2006), the use of computer-assisted learning became increasingly common as a tool in the anatomy classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory activities are considered as a fundamental tool to help students learn more effectively (16,27). Various types and designs of experimental sessions have been used, including the classical works and animal models (13,26). Practical classes are important, as they may reinforce learning of the basic content of lectures and texts, providing the student with an in-depth understanding of key and sometimes difficult concepts that serve as a basis for future medical practice.…”
Section: Table 2 Students' Evaluation Of the Use Of Practical Activimentioning
confidence: 99%
“…The regional distribution of normal pulmonary ventilation is heterogeneous, being higher in the dependent than the nondependent parts of the lungs, configuring a vertical gradient of ventilation. The main determinants of this physiological phenomenon include the geometry of the airway tree, the local regional respiratory compliance, and the effects of gravity (13). Body posture can influence the heterogeneity of pulmonary ventilation markedly (11).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 2 decades, there has been an increasing recognition in the physiology education literature as to how innovative interventions can be used to address such issues ranging from case-stimulated and problem-based learning (27,28), patient-centered learning (26), multiple format sessions (13), early clinical exposure (17), acting out concepts (10,30), use of educational puzzles and card games (13,15), and use of classical papers and animal models, both virtual and live (12,23).…”
mentioning
confidence: 99%